Disruption of the Gene trx-m1 Impedes the Growth of Anabaena sp. PCC 7120 under Nitrogen Starvation. (8th April 2019) - Deschoenmaeker, Frdric; Mihara, Shoko; Niwa, Tatsuya; Taguchi, Hideki; Nomata, Jiro; Wakabayashi, Ken-Ichi; Hisabori, Toru
Abstract: Cyanobacteria possess a sophisticated photosynthesis-based metabolism with admirable plasticity. This plasticity is possible via the deep regulation network, the thiol-redox regulations operated by thioredoxin (hereafter, Trx). In this context, we characterized the Trx- m 1-deficient mutant strain of Anabaena sp., PCC 7120 (shortly named A .7120), cultivated under nitrogen limitation. Trx- m 1 appears to coordinate the nitrogen response and its absence induces large changes in the proteome. Our data clearly indicate that Trx- m 1 is crucial for the diazotrophic growth of A .7120. The lack of Trx- m 1 resulted in a large differentiation of heterocysts (>20% of total cells), which were barely functional probably due to a weak expression of nitrogenase. In addition, heterocysts of the mutant strain did not display the usual cellular structure of nitrogen-fixative cells. This unveiled why the mutant strain was not able to grow under nitrogen starvation.